The impossible dead - Rankin, Ian (Little, Brown and Company, 2011)
A major inquiry into a neighboring police force sees Malcolm Fox and his colleagues cast adrift, unsure of territory, protocol, or who they can trust. An entire station-house looks to have been compromised, but as Fox digs deeper he finds the trail leads him back in time to the suicide of a prominent politician and activist. There are secrets buried in the past, and reputations on the line.